Multi-source task scheduling in grid computing environment using linear programming. (1st January 2014) - Murugesan, G.; Chellappan, C.
In grid computing environment the workload can be submitted by various grid users. Allocating a load to the resources from various grid users is a challenging task in grid scheduling process. So we need a better resource allocation framework to schedule the tasks from various sources to the dynamic resources. This paper introduces a new divisible load scheduling framework to map the task to the distributed resources in grid computing environment. We have developed a mathematical model to allocate tasks to resource when the task is submitted by various grid users (sources) with the aim of minimising the completion time of scheduling process with satisfying the budget allotted by the grid user based on divisible load theory. This model helps to estimate the resource usage cost of each source under the fluctuation of resource availability and the performance evaluation of three resource homogeneous resources and the link capacity is presented.